The Management of Medical Support Troops in the Battle of Kursk - V. P. Gridnev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article, based on archival materials, memoirs of participants of the great Patriotic war and other sources, analyzes the organizational activities of the Military councils of fronts and armies during the period of the battle of Kursk medical support of troops. Considered the activities of the authorities front-line areas aimed at the realization of the call of the homeland “Everything for front, everything for Victory!”. This and the provision of broad assistance to the wounded soldiers, including the deployment of hospitals and the patronage of them, and the establishment of health Foundation of defenders of the homeland, organization of donor movement, and providing food, utensils, furniture, etc. the battle of Kursk teaches that the unity of the front and rear is the main and decisive condition for the Victory of the people over the aggressor.